Pengaruh Pembelajaran Inquiry Berbantuan Video Animasi terhadap Minat Belajar dan Pemahaman Matematika SD - Fauzia, Novia Alifah; Masjudin; Yuntawati (Media Pendidikan Matematika, 2025)
This study aims to examine the impact of an inquiry-based learning model supported by animated videos on elementary school students’ learning interest and conceptual understanding in mathematics. The background of this research highlights difficulties in mathematical literacy at SDN 4 Pringgabaya, particularly in geometry, which may stem from the conventional teaching methods commonly used. The research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. A total of 50 fifth-grade students from SDN 4 Pringgabaya participated in the study, divided into two groups: the experimental group, which received inquiry-based learning with animated video support, and the control group, which received conventional instruction. The instruments used were a learning interest questionnaire and a conceptual understanding test, both administered as pretests and posttests. Data were analyzed using the Shapiro-Wilk normality test, Independent Samples T-Test or Mann-Whitney U for hypothesis testing, and the N-Gain test to measure improvement. The findings reveal that the inquiry-based learning model with animated video support had a significant effect on students’ learning interest (Sig. 0.000 < 0.05). However, the impact on conceptual understanding did not reach statistical significance (Sig. 0.411 > 0.05), likely due to initial differences in student ability between the groups. Nonetheless, the N-Gain analysis showed a medium-to-high improvement in the experimental group (0.6826), while the control group remained in the low category (0.0498). Thus, the model proved effective in increasing students’ interest in learning and had a positive impact on their mathematical conceptual understanding.